Pengaruh manfaat, kepercayaan, kemudahan penggunaan, dan keamanan terhadap persepsi konsumen dalam pembayaran elektronik BRI mobile pada mahasiswa - Lola Yolanda; Whyosi Septrizola (Jurnal Kajian Manajemen dan Wirausaha, 2021)
The purpose of this study was to analyze: (1) The effect of benefits on consumer perceptions of BRI Mobile on students in the city of Padang, (2) The effect of trust on consumer perceptions of BRI Mobile for students in the city of Padang, (3) The effect of ease of use on consumer perceptions of BRI Mobile for students in the city of Padang, and (4) The effect of security on consumer perceptions of BRI Mobile on students in the city of Padang. This type of research is a quantitative research. The population of this research isan unknown number of students in the city of Padang use BRI Mobile. The method used is purposive sampling method. The number of samples is 100 people. The data used are primary and secondary data obtained through distributing questionnaires to students in the city of Padang. The analytical method used is descriptive analysis through multiple regression analysis. The results showed that: (1) Benefits affect the perceptions of BRI Mobile consumers on students in the city of Padang, (2) Trust affects the perceptions of BRI Mobile consumers on students in the city of Padang, (3) Ease of use affects the perceptions of BRI Mobile consumers on students in the city of Padang, and (4) Security has no effect on consumer perceptions of BRI Mobile among students in the city of Padang. Keywords: Consumer perceptions, benefits, trustworthiness, ease of use, security